Mesothelioma Diagnostics, Treatment and Basic Research - Strumfa, Ilze (IntechOpen, 2022)
This book is devoted to the state of the art, pitfalls and perspectives in the diagnosis and treatment of mesothelioma - a peculiar malignant tumour arising from mesothelial cells that line the pleura, the pericardium and the peritoneum. Mesothelioma is known for its strong association with asbestos exposure, difficult surgical treatment and dismal prognosis. However, recent years have yielded significant discoveries on, for example, germline mutations in BAP1 gene coding BRCA1-associated protein 1, the pathogenetic role of inflammation, and innovative treatment approaches such as immune checkpoint inhibitors. The volume is intended to summarise classic views and innovations in the pathogenetic concepts, diagnostics, treatment and scientific studies of mesothelioma, resulting in a comprehensive reference work as well as a source of ideas for relevant clinical and basic research.